The travel industry - Gee, Chuck Y. (John Wiley & Sons, 1996)
This innovative third edition focuses on topics of a more global nature, such as concepts of trade barriers as impediments to promoting international travel and tourism. Specific illustrations are offered on how government policies, including diplomatic recognition, will affect tourism trade relationships. The third edition also covers current U.S. policies and reciprocal acts to promote tourism exchanges with other countries, as well as a special section on the amusement, entertainment, and retail product aspects of tourism.